INTEGRASI TEOLOGI SALIB DAN PSIKOLOGI DALAM MENANGANI DEPRESI ROHANI - Legrans, Apriani Delfita; Brek, Yohan (PT. Giat Konseling Nusantara, 2025)
This article discusses the integration of the theology of the cross and psychology in addressing spiritual depression among Christians. Spiritual depression is understood as a form of spiritual suffering that is often neglected or misunderstood in church ministries, which tend to emphasize normative solutions without considering psychological aspects. Through a qualitative theologicalpastoral study, This article highlights the importance of interpreting suffering not as a failure of faith, but as a space for encountering God who suffers alongside humanity, as taught in the theology of the cross. On the other hand, the pastoral psychology approach provides a scientific framework for understanding and holistically healing inner wounds. The integration of these two disciplines encourages the church to offer empathetic, contextual counseling services that touch all dimensions of the human person: body, soul, and spirit. Thus, the church is expected to become a healing community that embodies the love and solidarity of Christ for those experiencing spiritual depression, while also eliminating the stigma against mental health disorders within the life of faith.